Analisis Perbaikan Produk NG Pada Proses Mixing dengan Metode Fault Tree Analysis (FTA) dan Failur Mode dnd Effect Analysis (FMEA) - Indra Gumelar; Tubagus Hendri (Jurnal Rekayasa Teknologi dan Sains Terapan, 2019)
PT. Sumi Rubber Indonesia as one of the biggest tire manufacturer in the world give full attention for the implementation of ISO/TS 16949 as a Harmonized global quality management system for the automotive industry (supply chain) based on ISO 9001:2008 + OEM (Original Equipment Manufacturing) specific requirement. It has more severa and detail request for Reduction of variation, defect, waste and field failure that would be indicator of company performance for quality improvement. The condition when was researching, there are some problem in mixing process which has ratio of product NG (Not Good) 1.96%, it is exceed than company target maximum of 1% from total production volume. To analyze all the potency of NG products along mixing process used Failure Mode and Effect Analysis (FMEA) method. This method could identify potential failure mode, potential failure cause, prevention and detection. Based on severity value, occurence and detection will obtain Risk Priority Number (RPN) as the reference of improvement priority. For deeply analysis, Fault Tree Analysis (FTA) used as supporting device to find out the root cause factor. By using these methods, ration of product NG can reduce become 0.96% that show the effectiveness of improvement.